Development of Mind Mapping Learning Media for Science Learning in Madrasah Ibtidaiyah - Fanny Fajria (MANDAILING GLOBAL EDUKASIA, 2026)
In elementary science education, traditional instructional methods often struggle to effectively convey abstract ecological interdependencies, necessitating the development of innovative visual learning media. This study aimed to develop and evaluate the feasibility and practicality of digital Mind Mapping learning media tailored for ecosystem topics in Madrasah Ibtidaiyah (Islamic elementary schools). Employing a Research and Development (R&D) approach, the study utilized the six-stage Luther development model: concept, design, material collecting, assembly, testing, and distribution. The interactive media was designed for Grade V students using a combination of FreeMind and Canva applications. The product’s feasibility was evaluated through rigorous expert validation, while its practical utility was assessed via a small-group trial involving five Grade V students at MIN 10 Aceh Besar. Data gathered through media validation sheets, material validation sheets, and student response questionnaires were analyzed descriptively using percentage-based criteria. The evaluation results demonstrated that the developed digital Mind Mapping media possesses exceptional instructional quality. The product achieved a media expert validation score of 92.5% and a material expert validation score of 89.28%, both positioning the media in the highly feasible category. Furthermore, the small-group trial yielded a student practicality score of 90.8%, confirming that the application is highly pragmatic for real-world classroom implementation. These findings suggest that the integration of digital Mind Mapping effectively bridges the gap between abstract science concepts and young learners' cognitive schemas. This study contributes a validated technological framework to primary science education, offering a scalable instructional alternative that optimizes conceptual organization and enhances student engagement.